Membangun Komunikasi Bisnis untuk Meningkatkan Perkembangan Usaha UMKM Telor Asin di Ds. Karang Harum - Andi Suhandi; Azmy Muhammad Habiby; Dede Nur Iskandar (JPPI: Jurnal Pengabdian Pelita Insani, 2025)
Abstract, There are so many obstacles faced by business actors, especially salted egg MSME businesses, where this type of food is mostly only produced by people who have already tried, so they have the obstacle of a lack of marketing communication skills. Even though in today's era, marketing communication skills are very much needed in order to reach a wider market area. The training provided by the academic team to salted egg MSME actors is very useful because communication skills in a business will be able to increase MSME income, increase MSME sales, and will function as an overall organizational marketing strategy.